2017
DOI: 10.1177/0886260517723142
|View full text |Cite
|
Sign up to set email alerts
|

Structural Pathways Between Race/Ethnicity, Substance Use, Military Service, and Male-Perpetrated Intimate Partner Violence in Pre-9/11 Military Families

Abstract: Along with service members, military families bear the brute consequences of global U.S. military intervention. Various studies have concluded that these deployments put military families at high risk for intimate partner violence (IPV). Using structural equation modeling (SEM) as a novel approach to examine IPV among pre-9/11 military families, this study considers variations of self-reported IPV from the point of the abused partner to test the impact of several life events and demographic factors on the type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…It is important to understand the dynamic ways in which behavior and substance use interact. Studies focused on IPV have investigated the social and psychological effects of alcohol on behavior (Caetano et al, 2004), substance use and racialized behaviors (Ballard et al, 2015; Cancio, 2017, 2018), and initial exposures to substance use and violence (Mandavia et al, 2016; Peinado et al, 2014). There are logical relationships connecting substance use and IPV, using selective disinhibition theory to contextualize the various gradations of substance use on the ability to maintain interpersonal relationships (Cancio, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to understand the dynamic ways in which behavior and substance use interact. Studies focused on IPV have investigated the social and psychological effects of alcohol on behavior (Caetano et al, 2004), substance use and racialized behaviors (Ballard et al, 2015; Cancio, 2017, 2018), and initial exposures to substance use and violence (Mandavia et al, 2016; Peinado et al, 2014). There are logical relationships connecting substance use and IPV, using selective disinhibition theory to contextualize the various gradations of substance use on the ability to maintain interpersonal relationships (Cancio, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Breiding et al (2014) found that Native American, Black, and multiracial non-Latino men had a significantly higher prevalence of sexual assault, battery, or stalking compared with White non-Latino men. Studies focused on IPV and military veterans have found that IPV does not manifest uniformly across groups of men of similar racial/ethnic groups (Cancio, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, other research has found gender differences in bystander behaviors, with women reporting more prosocial intervention behavior, or fewer missed opportunities, compared with men (Hoxmeier, Acock, & Flay, 2017;Hoxmeier, McMahon, O'Connor, 2017;Banyard and Moynihan, 2011;Brown et al, 2014;Burn, 2009). Scholars contend that any investigation into prosocial intervention behaviors should be measured relative to opportunities to intervene (McMahon et al 2015), a design not used in previous examination with the TTM.…”
Section: Rth Prosocial Bystander Intervention and Gendermentioning
confidence: 99%